2015
DOI: 10.1016/j.ejphar.2014.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone affects both endothelial and vascular smooth muscle cells in rat arteries

Abstract: Hypothyroidism impairs endothelium-dependent dilatations, while hyperthyroidism augments the production of endothelial nitric oxide. Thus, experiments were designed to determine if thyroid hormone causes endothelium-dependent responses, or alleviates diabetic endothelial dysfunction. Isometric tension was measured in rings with or without endothelium of arteries from normal and diabetic Sprague-Dawley rats. Release of 6-keto prostaglandin F1α and thromboxane B2 were measured by enzyme linked immunosorbent assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 78 publications
2
28
2
Order By: Relevance
“…Similarly, studies using isolated rat aortas have demonstrated that T3 induces endothelium-dependent vascular relaxation [20]. However, conflicting reports in the literature have demonstrated that T3 does not causes vasorelaxation per se , and that only high concentrations of T3 are able to causes relaxation in small vessels such as mesenteric and femoral arteries [10]. In this present study, we found that aortas acutely stimulated with T3 do not cause relaxation by itself but markedly potentiated vascular relaxation in response to vasoactive agents ACh and SNP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, studies using isolated rat aortas have demonstrated that T3 induces endothelium-dependent vascular relaxation [20]. However, conflicting reports in the literature have demonstrated that T3 does not causes vasorelaxation per se , and that only high concentrations of T3 are able to causes relaxation in small vessels such as mesenteric and femoral arteries [10]. In this present study, we found that aortas acutely stimulated with T3 do not cause relaxation by itself but markedly potentiated vascular relaxation in response to vasoactive agents ACh and SNP.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, others and our group have demonstrated that T3 also potentiates vascular relaxation via endothelium-independent mechanisms, suggesting that VSMC are a new target for T3-mediated vasodilation [10, 13]. The mechanisms underlying the rapid effects of T3 in mediating vascular relaxation remain poorly explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid hormones have been shown to act directly on coronary artery smooth muscle cells [25] and rat mesenteric arteries [26] to induce vasodilation in a non-genomic manner, occurring within a few minutes of stimulation [17]. The mechanism and receptors responsible for T3 mediated dilation is emerging in the literature, with one recent study in TR␣ knockout mouse mesenteric arteries lacking the T3 vasodilatory effect.…”
Section: Interactions Of Ligands With Trˇ and Trtmentioning
confidence: 98%
“…We have demonstrated TH-induced rapid nitric oxide (NO) production in vascular smooth muscle (VSMC) via PI3K/Akt signaling, suggesting involvement of this pathway in TH mediated vascular relaxation [2]. Cai et al also observed that TH rapidly promotes vasorelaxation, with VSMC being a primary target of this hormone [3]. Inadequate TH production (hypothyroidism) is linked to impaired vascular reactivity and endothelial dysfunction [4].…”
mentioning
confidence: 99%